Learning via television cartoon - Abd Rahim, Normaliza; Abdul Halim, Hazlina; Mamat, Roslina (Canadian Center of Science and Education, 2014)
Cartoons have been a favorite among children, teenagers and adults. Cartoons began with paper drawing and have evolved to the highest technology of dissemination in the form of movies; apart from that, cartoons have become a teaching tool for second language learners. The objectives of the study were to identify and discuss the characters, storyline and moral values in a Malay cartoon. The cartoon used in this study was Upin and Ipin. The samples consist of ten subjects from a Malay language proficiency class at one of the universities in Korea. The subjects viewed 8 episodes of Upin and Ipin for 1 hour a week for a total of 8 weeks. The subjects were interviewed based on their views about the cartoon. The results of the study revealed that the subjects managed to identify all of the characters in the cartoon. The subjects also understood the storylines in six episodes of the cartoon. Moreover, the results revealed that the moral values for each episode involved respect, hardworking, caring, loving and others. This study implicates educators to consider cartoons as a teaching tool in foreign language learning. It is hoped that a future study will focus on cartoons when learning to write short stories among Malay language learners.